2020
DOI: 10.1002/advs.202000681
|View full text |Cite
|
Sign up to set email alerts
|

EGF Relays Signals to COP1 and Facilitates FOXO4 Degradation to Promote Tumorigenesis

Abstract: Forkhead-Box Class O 4 (FOXO4) is involved in critical biological functions, but its response to EGF-PKB/Akt signal regulation is not well characterized. Here, it is reported that FOXO4 levels are downregulated in response to EGF treatment, with concurrent elevation of COP9 Signalosome subunit 6 (CSN6) and E3 ubiquitin ligase constitutive photomorphogenic 1 (COP1) levels. Mechanistic studies show that CSN6 binds and regulates FOXO4 stability through enhancing the E3 ligase activity of COP1, and that COP1 direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…After incubation in 70% ethanol overnight, the samples were embedded in paraffin. Paraffin-embedded sections were stained with hematoxylin and eosin according to standard procedures [24,25] and a certified pathologist counted the mitotic cells under high-power fields (40 × magnification).…”
Section: Histologic Staining and Mitosis Countmentioning
confidence: 99%
“…After incubation in 70% ethanol overnight, the samples were embedded in paraffin. Paraffin-embedded sections were stained with hematoxylin and eosin according to standard procedures [24,25] and a certified pathologist counted the mitotic cells under high-power fields (40 × magnification).…”
Section: Histologic Staining and Mitosis Countmentioning
confidence: 99%
“…FOXO4 is a suppressor in cancers. Nevertheless, recent studies have shown that FOXO4 is also a tumor promoter ( Li et al, 2016 ; Choi et al, 2020 ; Wang et al, 2021 ); for example, the upregulated FOXO4 could inhibit the invasive and metastatic characteristics of cholangiocarcinoma cells by regulating focal adhesion kinase and F-actin dynamics. FOXO4 upregulation was in response to chemotherapeutic treatment in B-cell lymphoma, which is associated with a poor prognosis ( Lee et al, 2009 ; Ryu et al, 2017 ; Jiang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolomics progress was performed based on a standard method as described previously [ 15 , 16 ]. In short, standards were diluted at a concentration of 5.0 mg/ml.…”
Section: Methodsmentioning
confidence: 99%